Faith In God and Implications for Believers: A Comparative Survey of Islam and African Indigenous Religions - Hussein I.I. Ibrahim; Mustapha Abdullah Kuyateh (Refleksi: Jurnal Kajian Agama dan Filsafat, 2024)
Most Muslims, including even Africans who accepted the faith, seem to have cultivated the same attitude of mind that African Indigenous Religions are not monotheistic in any form. Non-Muslim Africans, who have kept to their indigenous heritage, are seen as bereft of any abiding values; they have no culture because any culture other than Islam is no culture. Therefore, all Africans who wanted to become Muslims were often prevailed upon to shed their traditional culture and take on the Islamic culture. In some communities in Northern Ghana, Muslims are looked upon and described as “white” contrasted with non-Muslim indigenes who are labeled “black”. The colours here refer to knowledge and lack of knowledge. It is for this reason that this paper takes up the issue to see whether the indigenous religions of Africa, like Islam, are not God friendly and whether, like Muslims also, the knowledge of God, as held by Africans, do have implications for believers. The essay intends to look at the concept of God in both Islam and African Traditional Religions and go on to examine some implications of this belief on individual believers of these two faiths.